2007
DOI: 10.1152/jn.00716.2007
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Amiloride-Sensitive Sodium Current and Voltage-Gated Calcium Currents in Rat Fungiform Taste Cells

Abstract: Bigiani A, Cuoghi V. Localization of amiloride-sensitive sodium current and voltage-gated calcium currents in rat fungiform taste cells. J Neurophysiol 98: 2483-2487, 2007. First published August 8, 2007 doi:10.1152/jn.00716.2007. Recent studies have shown that taste cells transducing bitter, sweet, and umami stimuli do not possess highthreshold voltage-gated calcium channels required for synaptic transmission at conventional synapses, suggesting some sort of signal processing inside taste buds prior to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…Yet, OXT was reported to decrease transepithelial amiloride-sensitive Na currents (ASSCs), thought to represent salt taste transduction [44]. Interestingly, salt taste detection and the underlying ASSCs may be limited to a subset of Glial-like cells [45], [46]. Consistent with this, salt-sensing taste cells were reported to be distinct from those that sense sweet, bitter, and umami stimuli (i.e.…”
Section: Discussionmentioning
confidence: 86%
“…Yet, OXT was reported to decrease transepithelial amiloride-sensitive Na currents (ASSCs), thought to represent salt taste transduction [44]. Interestingly, salt taste detection and the underlying ASSCs may be limited to a subset of Glial-like cells [45], [46]. Consistent with this, salt-sensing taste cells were reported to be distinct from those that sense sweet, bitter, and umami stimuli (i.e.…”
Section: Discussionmentioning
confidence: 86%
“…Amiloride-sensitive Na + currents have been reported in taste bud cells that are neither type II or type III cells, based on their lack of voltage-gated currents 82 . By contrast, a report from another group demonstrated that the amiloride-blocked resting conductance was most prominent in cells that had the characteristics of type II cells 83 . Neither of these studies pinpointed the ENaC-mediated currents to cells that could be identified by type-specific molecular markers.…”
Section: Chemosensory Transductionmentioning
confidence: 80%
“…We found co-expression of ghrelin with the ENaC α- and γ subunits and we also found reduced numbers of cells containing ENaC subunits in GHSR null mice. Taste cells expressing functional AS channels have also been shown to possess large voltage-gated sodium currents that underlie the generation of action potentials [55]. A third study has demonstrated that AS cells can generate action potentials and express ENaC subunits, suggesting that AS cells may be taste cells distinct from Type I cells without action potentials [56].…”
Section: Discussionmentioning
confidence: 99%